AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DALAM UPAYA MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA BATUBINTANG KECAMATAN BATUMARMAR KABUPATEN PAMEKASAN 2021 - Moh Yasin, Abd Hakim; M. Bashri Asy’ari (Institut Agama Islam Negeri (IAIN) Madura, 2023)
Allocation of Village Funds (ADD) as stimulant assistance or stimulus funds to encourage financing programs for administering village governance, implementation of development, community development, and community empowerment. This study aims to analyze the application of Village Fund Allocation (ADD) accountability in an effort to improve community development and empowerment in Batu bintang Village, Batumarmar District, Pamekasan Regency. This research uses a descriptive qualitative approach, namely data collected in the form of words, pictures, and not numbers, take advantage of the scientific method and use a field export approach, the data needed by observation, interviews, documentation and others. The results of this study are 1. Implementation of Village Fund Allocation (ADD) management accountability in Batu bintang Village, Batumarmar District, Pamekasan Regency. A. Transparency. The transparency in question is completing the village apparatus towards the community in the implementation of ADD. B. Accountable. Accountable in question is the planning, implementation and evaluation in the implementation of ADD. C. Participatory. Participative means that in the implementation of ADD, the community also participates in the planning and evaluation based on the MusDes. 2. Implementation of village fund allocation management accountability (ADD) in an effort to increase community development and empowerment in Batu bintang Village, Batumarmar District, Pamekasan Regency. A. Infrastructure. The infrastructure in question is building roads, repairing halls and making ditches. B. Countermeasures against Covid-19 posts. The handling of the Covid-19 post is intended to facilitate interaction between the community and officers related to handling Covid-19.